THE EFFECT OF “TEGAR” COMPLEMENTARY EDUCATION PACKAGES ON SELF EFFICACY AND ANXIETY IN POST ABORT MOTHER - Rahmayanti, Rini; Wahyuni, Fitri; Puspasari, Dwi (E-Jurnal Medika Udayana, 2023)
Abortion is a maternal emergency with an incidence of 10-15% of 6 million pregnancies each year. Self efficacy is one of the main factors to improve coping behavior towards perceived loss. The mother's inability to deal with problems causes prolonged grief and affects future health, so efforts are needed to increase self-efficacy and reduce maternal anxiety. Mother's self-efficacy and anxiety are influenced by knowledge. Increased knowledge can be done by providing a complementary package of interventions "TEGAR". This study uses a pre-experimental design method with a One-Group Pre-Post test design approach. The study was conducted for six months in RSUD dr. Rasidin Padang with a sample of 22 mothers who experienced spontaneous abortion during the last three months. The instrument that will be used is a questionnaire. The results of the study will be processed with a paired T-test statistical test. The results showed that the mean value of Self Efficacy before being given the intervention was 23.82 and after being given the intervention was 64.32. The average value of anxiety before being given the intervention was 64.32 and after being given the intervention was 41.41. There is a difference in the mean value between before and after the intervention was given with a p-value of 0.000. It is hoped that health services can use complementary education packages as a therapy to increase self-efficacy and reduce maternal anxiety after abortion.